Rancangan Strategi Employer Branding PT XYZ Periode 2024 - 2025: SettingsIrfan Rakan Hermanto, Noveri Maulana - Hermanto, Irfan Rakan; Noveri , Maulana (Universitas Bojonegoro, 2024)
One of the main challenges faced by large companies today is meeting the growing demand for talent, as the success and sustainability of companies depend on workforce quality. Employer branding has emerged as an effective approach to attract and retain top talent in an increasingly competitive environment. This study aims to design an Employer Branding strategy for PT XYZ for the 2014-2025 period. A descriptive qualitative method was used in the form of a case study, with data sourced from both primary and secondary sources. Primary data were collected through interviews, surveys, and participant observation, while secondary data came from literature reviews. The results indicate that companies can enhance Employer Branding by analyzing gaps between the EVP values desired by candidates and the Employer Branding strategies of competitors. Future research can build upon these findings to further explore the development of Employer Branding strategies.